Analisis Bibliometrik Tren Penelitian Penggunaan Gadget, Pola Tidur, dan Kesehatan Mental: Studi Berdasarkan Data Dimensions dan Publish or Perish (2020–2026) Menggunakan VOSviewer - Baiq Amalia Sholiha; Herni Sulastien; Diny Kusumawardani (Fakultas Ilmu Kedokteran dan Ilmu Kesehatan, Universitas Warmadewa, 2026)
Abstract The rapid increase in gadget use in recent years has impacted sleep patterns and mental health, particularly in children and adolescents. This study aims to map research trends related to this topic through bibliometric analysis. Data were obtained from Dimensions (30 articles) and Publish or Perish (866 articles) for the period 2020–2026. Analysis using VOSviewer produced three visualizations: network, overlay, and density. The network visualization results revealed five main clusters: gadget use, sleep disorders, mental health, special populations, and the COVID-19 pandemic. The overlay visualization shows a shift in research focus from the pandemic (2020–2022) to gadget addiction and sleep quality (2023–2026). The density visualization highlights dense keywords such as child, gadget use, addiction, and sleep pattern. These findings provide a comprehensive overview of global research directions and can inform public health interventions to limit screen time and promote healthy sleep habits. KEYWORD : Bibliometrics; Gedget ; Mental Health; Sleep Patterns; VOSviewer